Activin/follistatin system in grass carp pituitary cells: - Regulation by local release of growth hormone and luteinizing hormone and its functional role in growth hormone synthesis and secretion. - Roger S K Fung; Jin Bai; Karen W Y Yuen; Anderson O L Wong (PLoS ONE)
Gonadotrophin regulation by activin/follistatin system is well-documented, but the corresponding effect on growth hormone (GH) has not been fully characterized and with little information available in lower vertebrates, especially in fish models. In grass carp, local interactions of GH and luteinizing hormone (LH) can induce GH release and gene expression at pituitary level via autocrine/paracrine mechanisms. To shed light on the role of activin/follistatin system in GH regulation by local actions of GH and LH, grass carp activin βA and βB were cloned, shown to be single-copy genes expressed in the pituitary, and confirmed to encode activin proteins capable of transactivating promoter with activin-responsive elements. In grass carp pituitary cells, activin A and B were effective in reducing GH secretion and GH cell content with concurrent drop in GH mRNA level whereas the opposite was true for follistatin, the activin-binding protein known to neutralize the effects of endogenous activin. Treatment with activin A and B not only could suppress basal but also inhibit GH mRNA expression induced by GH and human chorionic gonadotropin (hCG), a functional analogue of LH in fish model. Apparently, down-regulation of GH mRNA by activin was mediated by reducing GH transcript stability with concurrent inhibition on GH promoter activity via the SMAD pathway. In reciprocal experiments, GH treatment was found to up-regulate activin βA, activin βB and follistatin mRNA levels in carp pituitary cells but the opposite was noted by removing endogenous GH with GH antiserum. Interestingly, parallel treatment with hCG could also inhibit basal as well as GH-induced activin βA, activin βB and follistatin gene expression. These results, as a whole, indicate that the pituitary activin/follistatin system can serve as a regulatory target for local interactions of GH and LH and contribute to GH regulation by autocrine/paracrine mechanisms in the carp pituitary.